The social construction of state power : applying realist constructivism - Barkin, J. Samuel, 1965- (Bristol : Bristol University Press, 2020)
Realism and constructivism are often viewed as competing paradigms for understanding international relations, though scholars are increasingly arguing that the two are compatible. Edited by one of the leading proponents of realist constructivism, this volume shows what realist constructivism looks like in practice by innovatively combining exposition and critiques of the realist constructivist approach with a series of international case studies. Each chapter addresses a key empirical question in international relations and provides important guidance for how to combine both approaches effectively in research. Addressing future directions and possibilities for realist constructivism in international relations, this book makes a significant contribution to the theorizing of global politics.
Realist constructivism: an introduction / Samuel Barkin -- Causation in realist constructivism: interactionality, emergence, and the need for interpretation / Germán C. Prieto -- Constructivist and neoclassical realisms / Samuel Barkin ; Huadu: a realist-constructivist account of Taiwan's anomalous status / Martin Boyle -- The India-U.S. nuclear deal: norms of power and the power of norms / Saira Bano -- How engagement works: lessons from U.S. policy toward China / Chi-hung Wei -- Taking co-constitution seriously: explaining an ambiguous U.S. approach to Latin America / Justin Delacour -- The bridging capacity of realist constructivism: the normative evolution of human security doctrine and the responsibility to protect / Andreea Iancu -- Permutations and combinations in theorizing global politics: whither realist constructivism? / Laura Sjoberg -- Saving realist prudence / Stefano Guzzini.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Political realism; Constructivism (Philosophy); International relations; Réalisme politique; Constructivisme (Philosophie); Relations internationales; international relations; POLITICAL SCIENCE / International Relations / General; Constructivism (Philosophy); International relations; Political realism